miR-451 Loaded Exosomes Are Released by the Renal Cells in Response to Injury and Associated With Reduced Kidney Function in Human - Kumari, Manju; Mohan, Aradhana; Ecelbarger, Carolyn M.; Saxena, Anita; Gupta, Amit; Prasad, Narayan; Tiwari, Swasti (Frontiers in Physiology, 2020)
Micro-RNAs (miRs) encapsulated inside urinary exosomes (uE) have potential as early biomarkers. Previously, we reported that a rise in uE miR-451 predicted albuminuria in diabetic rats; however, whether the rise was protective or detrimental, and occurred in response to injury or general hyperglycemia, was unknown. To address this, we studied both human and rat models of renal disease. In humans, uE MiR-451 was 2-fold higher in subjects with early-stage chronic kidney disease (CKD, n=28), as compared to age-matched healthy controls (n=23), and had a significant negative correlation with estimated glomerular filtration rate, eGFR (r2=-0.10, p=0.01). Subgroup analysis of CKD subjects showed that those without diabetes had slightly ( 30%), but significantly higher uE miR-451, as compared to those with diabetes, with no differences in albumin excretion, eGFR, serum sodium, and potassium. Using human proximal tubule (hPT) cells, we found locked nucleic acid (LNA) inhibition of miR-451 resulted in a significant increase in the mRNA expression of kidney injury-associated miR-451 targets, e.g.,CAB39, TBX1, and YWHAZ, as compared to treatment with a control LNA. Moreover, hPT cells and their secreted exosomes showed an increase in miR-451 in response to mechanical injury, but not high glucose (20 mM vs. 5 mM). For further proof-of-concept, in diabetic rats, we showed Atorvastatin, a treatment proven to attenuate renal injury without affecting systemic glucose levels, reduced uE miR-451 with the concomitant restoration of renal miR-451. These data elucidate the stimuli for renal miR-451 expression and exosomal release and support its role as a therapeutic target and early biomarker for renal injury in humans.